2007
DOI: 10.1007/s10708-008-9119-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk in the Okavango Delta in the face of social and environmental change

Abstract: Information from 117 questionnaires and focus groups in four villages in the Okavango Delta, Botswana was used to identify households exposed to different levels of risk in order to relate them to various livelihood activities and coping strategies. Current household strategies such as migration and diversification that are used to cope with recurring hazards such as drought, reduced flooding and animal disease are becoming more limited because of fencing policies and changed flooding regimes. In the light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Furthermore, of the articles that indicated that women are more vulnerable than men (Wilk and Kgathi 2007; Nation 2010; Bokhoree et al 2012; Cassidy and Barnes 2012; Cherotich et al 2012; Drolet 2012; Maponya and Mpandeli 2012; Safi et al 2012), only a very few refer to their own data, that is, to their own evidence. The remaining statements were based on theoretical backgrounds and analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, of the articles that indicated that women are more vulnerable than men (Wilk and Kgathi 2007; Nation 2010; Bokhoree et al 2012; Cassidy and Barnes 2012; Cherotich et al 2012; Drolet 2012; Maponya and Mpandeli 2012; Safi et al 2012), only a very few refer to their own data, that is, to their own evidence. The remaining statements were based on theoretical backgrounds and analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Those papers, that did, concluded that policymakers and practitioners must consider the intra-household distribution of labour and resources, as well as agricultural and other household activities, in order to understand women’s vulnerabilities and adaptation processes. Wilk and Kgathi (2007) conclude their study by highlighting that there are both social and spatial differences in risk and these need to be better understood by policy makers in order to better target initiatives. Jerneck and Olsson (2013) call for inclusive and participatory processes, which reconsider and act upon the underlying, structural layers of poverty and the need for broader policies on social change.…”
Section: Discussionmentioning
confidence: 99%
“…4b however, only 15 % of all vulnerability assessments have used a statistical selection method. PCA is by far the most popular parameter selection method, used by Burton and Cutter (2008), Chen et al (2013), Kleinosky et al (2006), Rygel et al (2006), Vermaat and Eleveld (2012), Wilk and Kgathi (2007), and Xu et al (2011). Ge et al (2013) uses a PPC method.…”
Section: Parameter Selection Methodsmentioning
confidence: 99%
“…Household surveys are predominantly used in developing countries where census data is not available. The assessments of Ologunorisa (2004), Wilk and Kgathi (2007), Clement (2013), and Mmom and Aifesehi (2013), which use household surveys extensively, are all conducted in Sub-Saharan Africa), or where insufficient census data is available for a certain demographic or topic, which is the case of Wang et al as well as the livelihoods of the local fishing population that depend on it, to oil spills. These oil spills originate from the Itaqui-Bacanga port complex.…”
Section: Data Consideredmentioning
confidence: 99%
“…census or earth observation data. Examples of studies that assess vulnerability through household surveys in river deltas are IMHEN et al (2011) in the Mekong Delta, and Wang et al (2012) in the Yangtze River Delta Mmom and Aifesehi (2013) in the Niger Delta, and Wilk and Kgathi (2007) in the inland Okavango Delta. By investigating the level of awareness causation of peoples actions (e.g.…”
Section: Introductionmentioning
confidence: 99%